2019
DOI: 10.1111/bph.14575
|View full text |Cite
|
Sign up to set email alerts
|

Probe dependence of allosteric enhancers on the binding affinity of adenosine A1‐receptor agonists at rat and human A1‐receptors measured using NanoBRET

Abstract: Background and Purpose Adenosine is a local mediator that regulates a number of physiological and pathological processes via activation of adenosine A1‐receptors. The activity of adenosine can be regulated at the level of its target receptor via drugs that bind to an allosteric site on the A1‐receptor. Here, we have investigated the species and probe dependence of two allosteric modulators on the binding characteristics of fluorescent and nonfluorescent A1‐receptor agonists. Experimental Approach A Nano‐lucife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…VCP171 certainly did not markedly enhance the contribution of A 1 ‐receptors in the final response, with the possible exception of a small effect on heart rate. VCP171 does not produce a large enhancement of the affinity of adenosine at the rat A 1 ‐receptor (Cooper et al, ) and it is likely that the positive A 1 ‐receptor allosteric action of the VCP171 entity within the larger VCP746 molecule is not sufficient to overcome the apparently more potent effect of the adenosine moiety on adenosine A 2A ‐ or A 2B ‐receptors in the cardiovascular system. This finding points to the need swap adenosine for a more A 1 ‐selective agonist within any future bitopic ligands and to match carefully the concentration range over which the orthosteric and allosteric components operate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VCP171 certainly did not markedly enhance the contribution of A 1 ‐receptors in the final response, with the possible exception of a small effect on heart rate. VCP171 does not produce a large enhancement of the affinity of adenosine at the rat A 1 ‐receptor (Cooper et al, ) and it is likely that the positive A 1 ‐receptor allosteric action of the VCP171 entity within the larger VCP746 molecule is not sufficient to overcome the apparently more potent effect of the adenosine moiety on adenosine A 2A ‐ or A 2B ‐receptors in the cardiovascular system. This finding points to the need swap adenosine for a more A 1 ‐selective agonist within any future bitopic ligands and to match carefully the concentration range over which the orthosteric and allosteric components operate.…”
Section: Discussionmentioning
confidence: 99%
“…This finding points to the need swap adenosine for a more A 1 ‐selective agonist within any future bitopic ligands and to match carefully the concentration range over which the orthosteric and allosteric components operate. It is also worth pointing out that the probe dependence of allosteric modulators also needs to be considered (Cooper et al, ). For example, VCP171 does not produce a significant positive allosteric effect on the binding of capadenoson to the rat A 1 ‐receptor (Cooper et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the allosteric modulators had little effect on the binding of the fluorescent antagonist, they enhanced the affinity of both fluorescent and non-fluorescent agonists. Interestingly, at the rat A 1 receptor, VCP171 increased the maximal binding capacity (B max ) with all three fluorescent agonists but only significantly increased the affinity of AAG-ABEA-X-BY630 (Cooper et al, 2019).…”
Section: Gpcr Allosterismmentioning
confidence: 96%
“…While the allosteric modulators had little effect on the binding of the fluorescent antagonist, they enhanced the affinity of both fluorescent and non‐fluorescent agonists. Interestingly, at the rat A 1 receptor, VCP171 increased the maximal binding capacity ( B max ) with all three fluorescent agonists but only significantly increased the affinity of AAG‐ABEA‐X‐BY630 (Cooper et al, ). This increase in agonist‐specific affinity suggested that the allosteric modulators were allowing a larger proportion of the receptor population to adopt a high‐affinity, R*, confirmation.…”
Section: Gpcr Allosterismmentioning
confidence: 99%